Study of drug utilization and antimicrobial prescription pattern of indoor paediatrics cases in tertiary care hospital - Bamel, Vivek Virbhan; Shahani, Savita Ramesh; Mohanty, Nimain C. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Infectious disease represent a major cause of mortality and morbidity in India. Pattern of use of antibiotics need to be studied separately as they vary from adult, however there is limited data is available, Therefore the aim of our study is to observe the drug utilization and antimicrobial prescription pattern and drug utilization in department of pediatrics at our tertiary care hospital. Methods: This was a prospective observational study carried out among indoor patients admitted to paediatric ward after obtaining approval by Institutional Ethics Committee. Written informed consent obtained from a parent or legal guardian of participants. Results: 100 patients were enrolled. The maximum number of antibiotics were prescribed from cephalosporin class (75; 43.6%) out of which ceftriaxone (42;56%), Cefixime (20;26.6%), cefotaxim (11;14.6%), cefpodoxime (3;4%), cefazolin (1;1.33%). The majority of cephalosporins were prescribed in Gastrointestinal tract infections (60.66%) followed by respiratory (27.2%) and least in cvs (2.66%), secondly higher group of antimicrobial prescribed was from Aminopenicillin class accounting of (36; 21.9%) which includes amoxiclav (35;97.2%), ampicillin (1;2.7%) and other beta lactamase (3;1.7%) consisting meropenem (2;66.7%), piperacillin with tazobatcam (1;33.3%). The majority of aminopenicillin were prescribed in respiratory tracts infections and very less in other systems. Miscellaneous drugs used in respiratory conditions were bronchodilator, systemic steroid and nasal decongestant; in CNS disorders antiepileptic and diuretics; in cardiovascular disease NSAID, inotropic, antihypertensive, diuretics; in genitourinary tract infections alkalizing agent and steroid and in GIT disorders minerals, rehydration fluids, antispasmodic probiotic were used. Conclusions: We conclude that commonly prescribed drugs were from 3rd generation cephalosporins followed from extended spectrum penicillin with β lactmase inhibitor. Majority of the antimicrobials are used empirically.